Manipulation of Financial Statements Through the Use of Creative Accounting. Case of Romanian Companies - Safta, Ioana-Lavinia; Achim, Monica Violeta; Borlea, Sorin Nicolae (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
The manipulation of the information presented through financial statements could represent a significant red flag for suspected fraud. In our paper, we investigated the extent to which the Romanian companies resort to manipulation of information data presented through the reported annual financial statements. For this purpose, we used a group consisting of 62 non-financial companies listed on the Bucharest Stock Exchange for the analyzed period 2017- 2018. The results of our study show that a majority percentage of the Romanian companies (approx. 84%) resort to manipulation of information provided through financial statements. Following the analysis carried out by activity fields, the results show that the companies activating in the fields of tourism, constructions, trade and transport resort to the manipulation of financial statements in the percent of 100%, followed by the companies activating in the field of production (86%) and services (50%). Our results are extremely useful to the users of financial information who must acknowledge the risks that they are exposed to in their decision-making process.